Enhancing the Survival Rate of Sand Goby, Oxyeleotris marmorata (Blkr.), Larvae with Antibiotics - Effendi, Irzal; Hadiroseyani, Yani (Jurnal Akuakultur Indonesia, 2002)
ABSTRACTPenicillin G and streptomycin sulphate were administered for 18 days of rearing of sand goby larvae. 7'wo-days larvae (3,37-3,41 mm) were reared in 160 1 aerated water at stocking density of 50 fish/1.  Until 17 days of rearing period, the larvae were fed plankton (50-300 gm) at stocking density of 20-30 individual/mi, and at day 13-I8, were fed Artemia sp. (1-2 individual/ml).  During first seven days, penicillin G and streptomycin sulphate (1.000 IU/1 and 10 mg/1, respectively) were applied daily, and there after once every three days.  The fry which reared in media containing antibiotics exhibited higher survival rate (28,09%, compared to 3,3 1 %), than the control, whereas their growth was similar (1,09-1,53 mm). Keywords :  Antibiotics, survival rate, sand goby fish, Oxyeleotris marmorata  ABSTRAKAntibiotik penisilin G dan streptomisin sulfat telah digunakan dalam pemeliharaan larva ikan betutu selama 18 hari.  Larva umur 2 hari (3,37-3,41 mm) dipelihara dalain tangki berisi air sebanyak 160 1 yang diaerasi halus, dengan kepadatan 50 ekor/1.  Antibiotik diberikan kepada media pemeliharaan larva setiap hari pada 7 hari pertarna pemeliharaan dan selanjutnya setiap 3 hari sekaii hingga akhir pemeliharaan, sebanyak 1.000 IU/1 dan 10 mg/1 masing-masing untuk penisilin G dan streptomisin sulfat.  Pada hari pertama hingga ke- 1 7, larva diberi makan plankton berukuran 50-300 gm sebanyak 20-30 individu/ml, hari ke- 13 sampai 18 diberi Artemia sp. sebanyak 1-2 ekor/ml.  Larva yang dipelihara pada media berantibiotik memiliki kelangsungan hidup (28,09%) lebih tinggi dibandingkan dengan tanpa antibiotik (3,31%), sedangkan pertumbuhan panjang mutlaknya sama yaitu 1,09-1,53 mm.Kata kunci :  Antibiotik, kelangsungan hidup, ikan betutu, Oxyeleotris marmorata